2010
DOI: 10.5012/bkcs.2010.31.01.075
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Aminolysis of N,N-Diethyl Carbamic Ester of HOBt Derivatives

Abstract: The reaction of N,N-diethyl carbamates of 1H- [1,2,3]triazolo [4,5-b]pyridin-1-ol (4-HOAt) 7, 3H-[1,2,3]triazolo [4,5-b] and 6-nitro-1H-benzo[d][1,2,3]triazol-1-ol (NO2-HOBt) 12 with morpholine and piperidine in CH3CN underwent acyl nucleophilic substitution to give the corresponding carboxamide derivatives. The reactants and products were identified by elemental analysis, IR and NMR. We measured the kinetics of these reactions spectrophotometrically in CH3CN at a range of temperatures. The rates of morpholino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…14 The mechanisms of few aromatic nucleophilic substitution reactions have been investigated by performing theoretical calculations by other methods. 12,15 As extension to our previous work in the field of nucleophilic aryl substitution reaction, [16][17][18][19][20][21][22][23][24][25][26][27][28] this work suggests a mechanism for the reaction of phenyl 1-(2,4-dinitronaphthyl) ether (1) with 3-and 4-substituted aniline derivatives (2a-f) in dimethyl sulfoxide (DMSO) (Equation 1). The effect of substituents in the nucleophile on the rate was also discussed, and Hammett and Brönsted correlations were examined.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…14 The mechanisms of few aromatic nucleophilic substitution reactions have been investigated by performing theoretical calculations by other methods. 12,15 As extension to our previous work in the field of nucleophilic aryl substitution reaction, [16][17][18][19][20][21][22][23][24][25][26][27][28] this work suggests a mechanism for the reaction of phenyl 1-(2,4-dinitronaphthyl) ether (1) with 3-and 4-substituted aniline derivatives (2a-f) in dimethyl sulfoxide (DMSO) (Equation 1). The effect of substituents in the nucleophile on the rate was also discussed, and Hammett and Brönsted correlations were examined.…”
Section: Introductionmentioning
confidence: 59%
“…As extension to our previous work in the field of nucleophilic aryl substitution reaction, 16‐28 this work suggests a mechanism for the reaction of phenyl 1‐(2,4‐dinitronaphthyl) ether ( 1 ) with 3‐ and 4‐substituted aniline derivatives (2a‐f) in dimethyl sulfoxide (DMSO) (Equation 1). The effect of substituents in the nucleophile on the rate was also discussed, and Hammett and Brönsted correlations were examined.…”
Section: Introductionmentioning
confidence: 71%
“…Several studies have been reported that aryl 1-(2,4-dinitronaphthyl) ether (1a-h) were considered as good substrates toward SNAr reactions. [20][21][22][23][24][25][26][27][28][29][30][31][32][33] This is because 2,4-dinitro groups with respect to 1-chloro substituent in one of the two rings of naphthalene made it susceptible toward nucleophilic substitution, and stable activated complex(s) is formed. 34,35 In the present study, kinetic of the reaction of aryl 1-(2,4-dinitronaphthyl) ether (1a-h) (Ar = a, X = H; b, X = 4-OCH 3 ; c, X = 4-CH 3 ; d, X = 3-CH 3 ; e, X = 3-OCH 3; f, X = 4-Cl; g, X = 3-Cl; and h, X = 4-NO 2 ) with piperidine (2) in DMSO at 25 o C was examined Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our studies in the field of nucleophilic aryl and acyl reactions [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], we addressed kinetic studies of the leaving group ability of 1-hydroxybenzotriazole (HOBt) in two example: 1-(1-hydroxybenzotriazolyl)-2,4-dinitro-benzene 1 and 2-(1-hydroxy-benzotriazolyl) 5-nitro-pyridine 2. The kinetic studies of 1 and 2 with different amines such as morpholine, cyclohexylamine and aniline in methanol (MeOH), acetonitrile (AN) and toluene (Tol) will be measured.…”
Section: Introductionmentioning
confidence: 99%